Pharmacodynamic and Pharmacokinetic Drug Interactions between Fexuprazan, a Novel Potassium-Competitive Inhibitor, and Aspirin, in Healthy Subjects - JungJin Oh; Eunsol Yang; In-Jin Jang; Hyejung Lee; Hokyun Yoo; Jae-Yong Chung; SeungHwan Lee; Jaeseong Oh (MDPI AG, 2023)
Acid-reducing agents are commonly used for the prevention of aspirin-induced gastrointestinal complications such as peptic ulcers. As a novel potassium-competitive acid blocker, fexuprazan is expected to prevent aspirin-induced gastrointestinal complications. This randomized, open-label study aimed to evaluate the pharmacodynamic and pharmacokinetic interactions between aspirin and fexuprazan in healthy Koreans. Subjects randomized to the aspirin group received 500 mg aspirin in combination with 80 mg fexuprazan. For the fexuprazan group, fexuprazan 80 mg was administered alone and then in combination with aspirin 500 mg. Platelet aggregation inhibited by aspirin and the pharmacokinetic parameters of aspirin and fexuprazan were compared between monotherapy and combination therapy. A total of 22 subjects completed the study. The platelet aggregation-inhibitory activity and systemic exposure to aspirin were not significantly affected by fexuprazan coadministration. The systemic exposure of fexuprazan was decreased up to 20% by aspirin coadministration, which was not regarded as clinically meaningful considering the previously reported exposure-response relationship. In conclusion, there were no clinically relevant pharmacodynamic or pharmacokinetic interactions between aspirin and fexuprazan. This finding suggests the potential of fexuprazan for the prevention of aspirin-induced gastrointestinal complications, serving as a baseline for optimizing its therapeutic application with aspirin.